OFFICE DE-CLUTTER MEDIATES THE FACTORS AFFECTING EMPLOYEE PERFORMANCE IN THE PRODUCTION AND OPERATION DIVISION - FARIS FERDIANTO NOOR; SETIA TJAHYANTI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
The aims of this study is to analyze the effect of Supervisor Support and Self Efficacy on Employee Performance, with Office De-Clutter as a mediating variable in the Production & Operation Division of PT XYZ. This study employs a quantitative research method, with sample selection using non-probability sampling through a saturated sampling technique. Data were collected using a Likert-scale questionnaire distributed to respondents via Google Forms. The population and sample in this study consisted of 79 employees of the Production & Operation Division of PT XYZ. This study used Partial Least Squares Structural Equation Modeling (PLS-SEM) via SMARTPLS 4.0 for data analysis. The findings reveal that both Supervisor Support and Self Efficacy significantly impact Employee Performance. In addition, Supervisor Support and Self Efficacy also have a significant effect on Office De-Clutter. Furthermore, Office De-Clutter has a significant effect on Employee Performance. However, Office De-Clutter does not mediate the relationship between Supervisor Support and Employee Performance, whereas Office De-Clutter mediates the relationship between Self Efficacy and Employee Performance.